Understanding Teacher School Choice Preferences: What Matters Most for Teacher Deployment in Sierra Leone? (EdTech Hub Preprint, 2023)
This exploratory mixed-methods study investigates the factors that shape where teachers want to work in Sierra Leone. We identify five dominant factors: monetary incentives, school conditions, opportunities for professional development and support, school location, and relationships with the school and the community. Importantly, these factors combine to push and pull teachers to different locations. Moreover, the factors interact with individual teacher characteristics such as gender, family status, and experience to influence school choice preferences. This set of factors — and their interaction with certain teacher characteristics — continues to shape preferences as teachers move up the career ladder. Keywords: Teacher deployment, teacher preferences, Sierra Leone, teacher supply, remote schools An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Developing a national EdTech strategy - Coflan, Caitlin; Wyss, Natalie; Thinley, Sangay; Roland, Mark (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Rapport de l’échange de connaissances - Koomar, Saalim; Rasolohery, Hasiniavo; Oojorah, Avinash; Udhin, Waaiza (EdTech Hub, 2025)
This is a report on a knowledge exchange visit between the Ministry of National Education of Madagascar and the Mauritius Institute for Education. The visit focused on sharing lessons and discussing ongoing projects related to technology in education. Key objectives included presenting successes and challenges of distance learning, discussing pedagogical design and digital platforms, and exploring long-term collaboration. School visits provided insights into technology integration in classrooms and teacher experiences. The report details the workshop's activities, participants, and key points, emphasising the importance of data-driven projects, feedback mechanisms, and continuous evaluation. Recommendations for future collaboration include short-term actions like remote communication and training, medium-term initiatives like co-presenting at conferences and personnel exchange, and long-term goals like co-applying for regional research projects. Keywords: teacher professional development; Madagascar; Moodle; knowledge exchange; EdTech; pedagogy Ce rapport porte sur une visite d’échange de connaissances entre le Ministère de l’Éducation Nationale de Madagascar et le Mauritius Institute for Education. La visite avait pour objectif de partager les enseignements tirés et de discuter des projets en cours liés aux technologies éducatives. Les principaux objectifs comprenaient la présentation des succès et des défis de l’apprentissage à distance, la discussion sur la conception pédagogique et les plateformes numériques, ainsi que l’exploration d’une collaboration à long terme. Les visites d’écoles ont permis d’observer l’intégration des technologies en classe et l’expérience des enseignants. Le rapport détaille les activités de l’atelier, les participants et les points clés, en mettant l’accent sur l’importance des projets basés sur les données, des mécanismes de retour d’information et de l’évaluation continue. Les recommandations pour une future collaboration incluent : Actions à court terme : communication et formation à distance; Initiatives à moyen terme : co-présentation lors de conférences et échanges de personnel; Objectifs à long terme : candidature conjointe à des projets de recherche régionaux. Mots clés: formation pédagogique; Madagascar; Moodle; échange de connaissances; technologie dans l’éducation; pédagogie An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Rapport d’Observation du Testing BETA - Ranaivosamoelina, Tokiniaina; Rasolohery, Hasiniavo (EdTech Hub, 2025)
This is a report on the Beta testing of a digital learning platform and applications developed for the Ministry of Education in Madagascar. The project aims to train 16,000 teachers, with 2,000 utilising distance learning via tablets. The Beta user testing focused on the pedagogical relevance, usability, and ergonomics of the platform and two offline applications. Twenty-one teachers participated, evaluating tasks like launching applications, navigating content, accessing multimedia, and completing exercises / evaluations. Results showed significant improvement from the Alpha user testing, with high success rates for accessing and navigating modules. However, over 50% of users still found the platform difficult to use, particularly for login, navigation, and profile modification. The applications were generally functional but needed adjustments to content presentation and visual quality. Recommendations included simplifying the platform's interfaces, enhancing user guides, and addressing specific content issues. The document emphasises the importance of ongoing quality assurance and an iterative approach to refining the platform. Keywords: teacher professional development; Madagascar; Moodle; user testing Ce rapport porte sur le test Beta d’une plateforme d’apprentissage numérique et des applications développées pour le Ministère de l’Éducation à Madagascar. Le projet vise à former 16 000 enseignants, dont 2 000 via l’apprentissage à distance sur tablette. Les tests utilisateurs en phase Beta ont évalué la pertinence pédagogique, l’ergonomie et la convivialité de la plateforme ainsi que de deux applications hors ligne. Vingt et un enseignants ont participé, réalisant des tâches telles que le lancement des applications, la navigation dans les contenus, l’accès aux éléments multimédias et la réalisation d’exercices/évaluations. Les résultats montrent une amélioration significative par rapport aux tests Alpha, avec des taux de réussite élevés pour l’accès et la navigation dans les modules. Cependant, plus de 50 % des utilisateurs ont encore rencontré des difficultés, notamment pour la connexion, la navigation et la modification du profil. Les applications étaient globalement fonctionnelles, mais nécessitaient des ajustements dans la présentation des contenus et la qualité visuelle. Les recommandations incluent la simplification des interfaces de la plateforme, l’amélioration des guides utilisateurs et la correction de problèmes spécifiques liés aux contenus. Le document souligne l’importance de l’assurance qualité continue et d’une approche itérative pour affiner la plateforme. Mots clés: formation pédagogique; Madagascar; Moodle; test utilisateur An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Rapport d’Observation du Testing Alpha - Ranaivosamoelina, Tokiniaina; Rasolohery, Hasiniavo; Koomar, Saalim (EdTech Hub, 2025)
This document, details the Alpha user testing of a digital learning platform and educational applications for the Ministry of National Education of Madagascar, aimed at training 2000 teachers. Conducted in July 2024, the testing focused on functionality and accessibility. Twenty-nine testers, primarily web developers and instructional designers, used a Google Forms questionnaire to evaluate the platform and applications. The results showed that while the platform was generally functional, with most features validated, several areas needed adjustments, particularly in accessibility and specific functions like the quiz timer. The applications had more issues, with several features requiring fixes and accessibility being a significant concern. Key recommendations included diagnosing and fixing defective parts, restructuring modules for better accessibility, optimising multimedia file sizes, and creating a detailed user guide. The testing highlighted the need for improvements before the Beta testing phase with teachers. Keywords: teacher professional development; Madagascar; Moodle; user testing Ce document détaille les tests utilisateurs en phase Alpha d’une plateforme d’apprentissage numérique et d’applications éducatives développées pour le Ministère de l’Éducation Nationale de Madagascar, dans le cadre de la formation de 2 000 enseignants. Réalisés en juillet 2024, ces tests ont porté sur la fonctionnalité et l’accessibilité. Vingt-neuf testeurs, principalement des développeurs web et des concepteurs pédagogiques, ont évalué la plateforme et les applications via un questionnaire Google Forms. Les résultats ont montré que, bien que la plateforme soit globalement fonctionnelle avec la plupart des fonctionnalités validées, plusieurs ajustements étaient nécessaires, notamment en matière d’accessibilité et pour certaines fonctions spécifiques comme le minuteur des quiz. Les applications présentaient davantage de problèmes, plusieurs fonctionnalités nécessitant des corrections et l’accessibilité étant un défi majeur. Les principales recommandations incluaient le diagnostic et la correction des éléments défectueux, la restructuration des modules pour une meilleure accessibilité, l’optimisation de la taille des fichiers multimédias et la création d’un guide utilisateur détaillé. Ces tests ont mis en évidence la nécessité d’améliorations avant la phase de test Beta avec les enseignants. Mots clés: formation pédagogique; Madagascar; Moodle; test utilisateur An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Guide pour les administrateurs de la plateforme Formation À Distance - Rasolohery, Hasiniavo; Ranaivosamoelina, Tokiniaina (EdTech Hub, 2025)
This is a practical guide for administrators of the Formation À Distance (FAD) platform in Madagascar. The guide provides instructions on managing the platform, with a focus on evaluations and forums. It covers topics such as setting up different types of evaluations (quizzes, assignments), configuring forum settings, managing discussions, and moderating forums. It also includes best practices for both evaluations and forums, as well as security considerations. The document provides step-by-step instructions with screenshots for specific tasks like activating edit mode, adding activities or resources, setting up tests, and configuring forum parameters. It also includes a glossary of terms, references, and useful links. The guide is intended to help administrators effectively manage the FAD platform and support teachers and students in their online learning activities. Keywords: teacher professional development; Madagascar; Moodle; tablet; administrator guide Ceci est un guide pratique destiné aux administrateurs de la plateforme de Formation À Distance (FAD) à Madagascar. Il fournit des instructions pour la gestion de la plateforme, en mettant l’accent sur les évaluations et les forums. Il couvre des sujets tels que la configuration des différents types d’évaluations (quiz, devoirs), le paramétrage des forums, la gestion des discussions et la modération des forums. Il inclut également les meilleures pratiques pour les évaluations et les forums, ainsi que des considérations de sécurité. Le document propose des instructions détaillées, illustrées par des captures d’écran, pour des tâches spécifiques comme l’activation du mode édition, l’ajout d’activités ou de ressources, la mise en place de tests et le paramétrage des forums. Il comprend également un glossaire des termes, des références et des liens utiles. Ce guide vise à aider les administrateurs à gérer efficacement la plateforme FAD et à soutenir les enseignants et les élèves dans leurs activités d’apprentissage en ligne. Mots clés: formation pédagogique; Madagascar; Moodle; tablette; guide pour les administrateurs An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Factors Related to Teacher Absenteeism in Sierra Leone: Literature review - Vijil, Alejandra; McBurnie, Chris; Bellinger, Amy; Godwin, Katie; Haßler, Björn (EdTech Hub, 2023)
This report is one of several on the research project on the Impact of GIS-Supported Teacher Allocation in Sierra Leone (Hub-Led Research Programme 3). The education workforce is the most important school-level determinant of student learning. In Sierra Leone, the pupil-to-qualified-teacher ratio rises from 44:1 for schools in urban centres to 76:1 for schools in rural areas. Meanwhile, an average of a quarter of the workforce is absent from school on any given day. This informal literature review provides a summary of the most recent literature on teacher absenteeism, covering a wide range of low- and middle-income countries, including Sierra Leone, where the larger study is being undertaken. For the purposes of this review, we have focused on lessons learnt from sub-Saharan African studies that share similar education contexts and challenges as Sierra Leone. Based on the review, we hypothesise that distance from a teacher’s home to their school and their ability to choose which school they would like to work in impact teacher motivation, school attendance, and time on task. Efficient teacher allocation could improve each of these outcome estimates. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Enquête nationale sur la possession et les usages des technologies parmi les enseignants du primaire - Rasolohery, Hasiniavo; Mitchell, Joel (EdTech Hub, 2025)
This document presents a report of a national survey on technology ownership and usage among primary school teachers in Madagascar, conducted in 2023. The survey, a collaboration between EdTech Hub, the National Institute of Pedagogical Training (INFP), and the Ministry of National Education, aimed to gather reliable data on ICT deployment across Madagascar's 23 regions. Data was collected through quantitative surveys and qualitative focus groups involving 1403 educators. Key findings reveal that while 97% of educators own technological tools, basic mobile phones are most prevalent. Smartphone ownership is significant, but usage is largely limited to calls and SMS, indicating underutilisation of advanced features. Internet access is limited, with only 25.2% of teachers accessing it via smartphone. Electricity access is relatively high at 89%, primarily through the national grid and solar energy. The report highlights the need for ICT training to enhance teachers' digital skills and recommends deploying offline systems to overcome connectivity issues. It also emphasises adapting content for teachers with disabilities and considering the predominantly regional language usage in professional settings. Keywords: national teacher survey; technology access; technology use; Madagascar; primary school Ce document présente un rapport sur une enquête nationale menée en 2023 sur la possession et l’usage des technologies par les enseignants du primaire à Madagascar. Cette enquête, réalisée en collaboration entre EdTech Hub, l’Institut National de Formation Pédagogique (INFP) et le Ministère de l’Éducation Nationale, visait à recueillir des données fiables sur le déploiement des TIC dans les 23 régions du pays. Les données ont été collectées à travers des enquêtes quantitatives et des groupes de discussion qualitatifs impliquant 1 403 enseignants. Les résultats clés révèlent que, bien que 97 % des enseignants possèdent des outils technologiques, les téléphones mobiles basiques sont les plus répandus. La possession de smartphones est significative, mais leur utilisation se limite principalement aux appels et aux SMS, ce qui indique une sous-utilisation des fonctionnalités avancées. L’accès à Internet reste limité, avec seulement 25,2 % des enseignants l’utilisant via un smartphone. L’accès à l’électricité est relativement élevé (89 %), principalement via le réseau national et l’énergie solaire. Le rapport souligne la nécessité d’une formation aux TIC pour améliorer les compétences numériques des enseignants et recommande le déploiement de systèmes hors ligne pour pallier les problèmes de connectivité. Il met également l’accent sur l’adaptation des contenus aux enseignants en situation de handicap et sur la prise en compte de l’usage majoritaire des langues régionales dans les environnements professionnels. Mots clés: enquête nationale des enseignants; accès à technologie; utilisation de technologie; Madagascar; Moodle; école primaire An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

What Should Ministries of Education Prioritise When Crafting Their Edtech Strategies? - Thinley, Sangay (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at priorities for governments and ministries of education when crafting EdTech Strategies. Interest in developing EdTech strategies related to operational targets and outcomes has increased over the past few years, especially in response to the learning disruptions caused by the Covid-19 pandemic. Evidence suggests that countries with established EdTech strategies were better equipped to respond to the pandemic and its effects due to their advanced preparation and readiness for large-scale remote learning. We examine the key principles for EdTech strategies, including the importance of focusing on learning outcomes, inclusivity, teacher training, costs, and contextual needs, among other factors. We draw on EdTech Hub's work in supporting several governments in designing and implementing EdTech strategies, as well as broader evidence from the field, to offer practical insights. We share details of some of the most significant findings and engaging lessons EdTech Hub has learnt, such as prioritising consultative processes of strategy development while focusing on multi-modal, problem-driven EdTech solutions and interventions guided by a unifying educational goal. We highlight areas that require further research, in particular questions related to cost-effective approaches to improving global learning, how governments can develop dynamic and iterative strategies, and the role of private sector partnerships in the successful implementation of EdTech strategies. Keywords: EdTech; education technology; education strategy; best practices for EdTech; EdTech planning An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech for Out-of-School Children and Youth: A Rapid Evidence Review for the Southeast Asian Region - Barnes, Katrina; Mazari, Haani; Mitchell, Joel; Hayat, Amal; Zhao, Annette; Ullah, Noor; Emerusenge, Aime Parfait; D'Rozario, Jonny; Hinks, Jessica; Thinley, Sangay (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for out-of-school children and youth (OOSCY) in Southeast Asia. The review summarises how EdTech is currently being used with OOSCY learners in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech with different out-of-school learners. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for OOSCY, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for OOSCY. Key words: out-of-school children; rapid evidence review; RER; Southeast Asia; ASEAN; education technology; marginalised learners An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Note de conseils sur la plateforme numérique - Messa, Angele; Koomar, Saalim; Mitchell, Joel (EdTech Hub, 2025)
This document is a guidance note on digital platforms, specifically focusing on e-learning and the use of Opale and Moodle software. It aims to support the implementation of a digital learning platform in Madagascar. The report addresses questions and challenges faced by the Ministry of National Education in developing and deploying digital educational content. It covers various aspects of e-learning, including evaluation methods, content structuring, accessibility, interactivity, and technical requirements. Key topics include different evaluation models, types of e-learning evaluation (formative and summative), guidelines for using Opale, tablet specifications for online learning, ensuring course accessibility, and using Moodle both online and offline. The document also provides a checklist for ensuring quality in e-learning course development and implementation. Keywords: e-learning; Moodle; Opale; digital platform; accessibility; usability; Madagascar Ce document est une note d’orientation sur les plateformes numériques, avec un accent particulier sur l’e-learning et l’utilisation des logiciels Opale et Moodle. Il vise à soutenir la mise en place d’une plateforme d’apprentissage numérique à Madagascar. Le rapport aborde les questions et défis rencontrés par le Ministère de l’Éducation Nationale dans le développement et le déploiement de contenus éducatifs numériques. Il traite de divers aspects de l’e-learning, notamment les méthodes d’évaluation, la structuration des contenus, l’accessibilité, l’interactivité et les exigences techniques. Les principaux sujets incluent les différents modèles d’évaluation, les types d’évaluation en e-learning (formative et sommative), les recommandations pour l’utilisation d’Opale, les spécifications des tablettes pour l’apprentissage en ligne, l’accessibilité des cours et l’utilisation de Moodle en mode en ligne et hors ligne. Le document propose également une liste de contrôle pour garantir la qualité du développement et de la mise en œuvre des cours en e-learning. Mots clés: e-learning; Moodle; Opale; platforme numériques; accessibilité; usabilité; Madagascar An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

Cohort Learning Handbook - Nicholson, Bryony (EdTech Hub, 2024)
The Cohort Learning Handbook captures EdTech Hub’s approach to building cohorts on its Evidence-Led Entrepreneurship Course. The course aims to help entrepreneurs adopt and utilise evidence to learn and to scale their products and services. The Handbook is for individuals and organisations who support EdTech entrepreneurs (e.g., accelerators, entrepreneurship programmes, and funders). Building a cohort supports entrepreneurs to learn quickly and more confidently as a result of learning with, from, and alongside peers sharing the same experience. By ensuring that the learning journey is the most effective it can be, we ensure our work has the greatest impact. By facilitating a cohort journey for EdTech entrepreneurs, you can: - Leverage the unique power of a cohort to improve the learning experience and learning outcomes. - Diversify the support on offer. - Streamline and improve technical support that we often offer ventures. The handbook includes a list of resources and templates for you to use and covers a range of topics and practical suggestions from key principles and onboarding to graduation and supporting alumni. Keywords: cohort; community; learning; collective; incubators; accelerators An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Working Towards Education Success Using Data: A review of Ghana's journey towards improved learning outcomes using data - Radford, Kate; Ampofo, Rudolph (EdTech Hub, 2024)
The sub-Saharan Africa region is trapped in a learning crisis with devastating implications for children. The Covid-19 pandemic further exacerbated the situation, with children losing an estimated equivalent of an additional year’s learning. Not addressing the regional learning crisis will have a detrimental impact on economic development and well-being and risks restricting future national and regional economic growth and productivity and fuelling social unrest. Education research has shown that good quality education system data, when judiciously used, can support improved learning outcomes among a host of other positive impacts on national education systems. This case study is the first in a series documenting the journey of Ghana’s Ministry of Education towards the effective use of data to guide its decision-making for policy and practice. Keywords: data for decision making; data governance; data management; Ghana; education data systems; evidence-based policy An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Education Sector Analysis. Assessing the enabling environment for gender equality - Republic of Sierra Leone (UNICEF, IIEP - UNESCO, 2020)